Implementing SDG to Village Level by Integrating Social Capital Theory and Value Chain: (Case of Village Tourism Pentingsari in Yogyakarta, Indonesia) - Affandi, Roseno Aji; Permana, Aditya; Yani, Yanyan Mochamad; Mursitama, Tirta Nugraha (JAS (Journal of ASEAN Studies), 2019)
Since the publication of the 2030 blueprint, Sustainable Development Goals (SDGs) have been promoted as a global project. Many steps have been taken; however, until now, the achievement remains limited. This is due to the low understanding of SDGs from stakeholders at the local level, such as the village. This study examines how we can develop SDG awareness and implementation in the village level. This article argues that we need to look at two essential factors namely the notion of social capital and value chain management in order to fulfill SDGs at the local level. Arguably, social capital can be mobilized by the local leaders to socialize the importance of SDGs at the village level. Second, value chain management enables local leaders to manage sustainable economic activities at the village level. Hence, these two concepts eventually enhance the implementation of SDGs at the village level. This argument will be illustrated in the case of three tourism village development areas in Yogyakarta namely, Pentingsari in Sleman, Mangunan in Bantul, and Bleberan in Gunungkidul.Â